VALIDITY OF METHOD FOR DETERMINING DEOXYNIVALENOL THROUGH HIGH PERFORMANCE LIQUID CHROMATOGRAPHY WITH DETECTION IN THE ULTRAVIOLET INWHEAT SAMPLES - Lettieri Teixeira, Mário; Meneghello Fuentefria, Alexandre (Boletín Micológico, 2009)
With the purpose of evaluating the wheat grain and wheat flour contamination by Deoxynivalenol (DON) in the municipality of Chapeco-SC, and standardize an useful method to detect this mycotoxin by High Performance Liquid Chromatography (HPLC), six samples of wheat grains from different storage location, and one sample of wheat grain from the flour milling industry were obtained during in the month of august 2008. Samples belong to a corporation from Chapeco- SC that stores and processes wheat grains, flour and wheat middlings, among other products. The extraction has been carried out with methanol: water (100: 100 v / v), filtered paper filter and applied in immunoaffinity column specific DON. After the wash with water column, the toxin was eluted with methanol. The detection and quantification Deoxynivalenol in samples was carrid out through the method of HPLC in the UV -visible with detection 244 nm. The 6 analyzed samples of wheat grain showed DON levels within 7.0 and 10.1 ppb, while the wheat flour contained 90.2 ppb. DON contents in wheat grains and wheat flour are lower than the limits claimed by the studied corporated importers and the international legislation.